In vivo testing of mucus-permeating nanoparticles for oral insulin delivery using Caenorhabditis elegans as a model under hyperglycemic conditions - Ana L. Martínez-López; Carlos J. González-Navarro; Paula Aranaz; José L. Vizmanos; Juan M. Irache (Elsevier, 2021)
The aim was to evaluate the potential of mucus-permeating nanoparticles for the oral administration of insulin. These nanocarriers, based on the coating of zein nanoparticles with a polymer conjugate containing PEG, displayed a size of 260 nm with a negative surface charge and an insulin payload of 77 μg/mg. In intestinal pig mucus, the diffusivity of these nanoparticles (PPA-NPs) was found to be 20-fold higher than bare nanoparticles (NPs). These results were in line with the biodistribution study in rats, in which NPs remained trapped in the mucus, whereas PPA-NPs were able to cross this layer and reach the epithelium surface. The therapeutic efficacy was evaluated in Caenorhabditis elegans grown under high glucose conditions. In this model, worms treated with insulin-loaded in PPA-NPs displayed a longer lifespan than those treated with insulin free or nanoencapsulated in NPs. This finding was associated with a significant reduction in the formation of reactive oxygen species (ROS) as well as an important decrease in the glucose and fat content in worms. These effects would be related with the mucus-permeating ability of PPA-NPs that would facilitate the passage through the intestinal peritrophic-like dense layer of worms (similar to mucus) and, thus, the absorption of insulin.